TNFR2 is expressed by a discrete subset of epidermal T cells with an IL-17 gene signature during psoriasis - Jasmine Ahmed; Carolyn Matthews; Patricia Tulloch; William Lawler; Albert Mendoza; Mikaela Rhoiney; Julie M. Jameson (PLoS ONE, 2026)
Psoriasis is a chronic skin disease that results in scaly patches and affects 2–3% of people worldwide. Therapeutic treatment targets the TNF-α/IL-17 axis to disrupt keratinocyte hyperproliferation and inflammation. While more is known about the role of dermal αß and γδ T cells in IL-17 production, less is understood about the role of resident epidermal T cells. Here, we examine how TNF-α modulates epidermal γδ T cell activation and function. We show that a subset of activated epidermal γδ T cells expresses TNFR2 with or without TNFR1. Stimulation with TNF-α induces epidermal γδ T cells to produce IL-17 family cytokines and chemokines. Epidermal γδ T cells do not require TNFR1 or 2 for development or homing to the skin. Instead, TNFR2 plays roles in epidermal γδ T cell function skewing them toward a Tγδ17 phenotype during psoriasis. Investigation of the mechanisms by which TNF-α associated inflammation impacts epidermal γδ T cell function may help identify new cellular targets for immunotherapy or mark them as early regulators of skin inflammation.